Disruptive Voices and Bodies: Toward an Understanding of the Cuban Repa-Reggaeton Scene - Lavielle Pullés, Ligia; Favero, Paolo S. H. (Revista Musical Chilena, 2024)
One of the most influential socio-musical phenomena in the contemporary cultural and popular landscape of Latin America and the Caribbean emerges from the rise of genres known as urban music. In Cuba, the impact of reggaeton, trap, and, more recently, the so-called "reparto" genre is notable and continues to expand across diverse age groups. Since the late 20th century, this topic has sparked debates regarding its origins, its ties to the music industry, the role of women as both a theme and creators, and the defining characteristics of genres like reggaeton. However, less attention has been given to the dynamics of participation and creation among all the agents involved in this socio-musical activity. In this regard, we have found that adopting the post-subcultural concept of "scene" provides a better understanding of the relationships among consumers, distributors, creators/producers, and the overall participants within this ecosystem. Our research, rooted in the fields of the sociology of music and ethnography, dissects the components of what we call the repa-reggaeton scene in one of Cuba's most important cities. A microsocial perspective allowed us to understand how these actors organize their work and to access their ideologies, interests, and translocal dimensions. Likewise, we explored how macro-social phenomena, such as migration and COVID-19, have influenced this scene—trends that may reflect similar dynamics in other Cuban and Latin American musical contexts.